Gratitude and Adolescents' Mental Health and Well-Being: Effects and Gender Differences for a Positive Social Media Intervention in High Schools - Giacomo Bono; Taylor Duffy; Erin L. Merz (MDPI AG, 2023)
Gratitude interventions can provide cost-effective support for mental health to under-resourced schools. This study aims to better understand the effects of a promising intervention Bono et al. evaluated in 2020. Using a quasi-experimental design (where classes were assigned to a thanking app, gratitude curriculum, app + curriculum, or control condition), that evaluation found that the full (combined) intervention impacted students' self-reported trait gratitude, anxiety, and subjective well-being (SWB) over six weeks, compared against only the control condition. However, here, we evaluated the individual intervention components' effectiveness on students (N = 326) using multilevel modeling. As hypothesized, the full intervention impacted students' gratitude, anxiety, and SWB, compared to the control condition, but impacted SWB more than the app-only condition, suggesting that teaching gratitude science makes thanking more meaningful. Then, we examined if stress mediated these effects. Perceived stress partially mediated the relationships of gratitude with depression and SWB and fully mediated the relationship of gratitude with anxiety. Additionally, changes in perceived stress and SWB differed by gender. Finally, we qualitatively analyzed thanks exchanges during the intervention using informal content analysis and found themes of psychological safety-a critical feature neglected in other interventions. We conclude with recommendations for optimizing school gratitude interventions.